If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -1(-2 + 4x) = 23 -3 + (-2 * -1 + 4x * -1) = 23 -3 + (2 + -4x) = 23 Combine like terms: -3 + 2 = -1 -1 + -4x = 23 Solving -1 + -4x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -4x = 23 + 1 Combine like terms: -1 + 1 = 0 0 + -4x = 23 + 1 -4x = 23 + 1 Combine like terms: 23 + 1 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| 1/3(2x-1)=4(x/6+2) | | x*2*9=168 | | 240/y=12 | | x*2*8=168 | | x*2*7=168 | | x/80=6 | | x*2*14=168 | | x*2*y=168 | | 284=39-W | | 8x+4=12x-4 | | x/-2=-7-(-10) | | -3+6+5x=7x-8x | | -3(x+11)+259=31+30 | | -16t^2-100t+100000=0 | | (3/2)x-(5/6)+x=(1/2)x+(2/3) | | y=10(3u+1)(1-5u) | | f(-1)=3y^2+7y-2 | | -7x-10y=70 | | 5(3+x)-(8x+9)=-4x | | -6w+5=7(w-3) | | -3(v+2)=2v+24 | | 5v-12=78 | | 5y-9y= | | 2+z=4.5 | | 4X^2+4X+89=0 | | 3-2t=-9 | | 7(x+5)+5(2x+1)= | | -8u-24=7(u+3) | | s-s=s+4 | | x+3.6=-4.75 | | 2(2x-1)= | | 9-2=8-s |